Algorithmicized bodies: Account nurturing behaviors on Chinese short video platforms. - Quan, Yizhang (Big Data & Society)
Based on in-depth interviews with 18 Chinese TikTok account nurturers and three months of online ethnographic observation, this study reveals how platform algorithms reconstruct users' physical bodies. The research shows that users seeking platform visibility "voluntarily" accept systematic algorithmic modifications to their bodies. Users: (1) manipulate their physiological rhythms, forming an "algorithmic clock"; (2) correct body postures, developing highly precise "movement patterns"; and (3) utilize painful bodily experiences to create "suffering capital." I conceptualize these findings as the "algorithmicized body." These practices present a significant paradox. Users willingly accept and intensify their alienation while pursuing autonomy. They instrumentalize basic physiological functions as traffic resources. By analyzing this microprocess of self-exploitation, the research reveals how platform algorithms not only control behavior as disciplinary devices but also penetrate and reshape users' physiological foundations and perceptual systems. The study extends disciplinary theory to algorithmic environments and offers important insights for platform design ethics and user rights protection.